The Unified Patent System – Expectation and Prospects for a United Europe - Maneva, Veselina (Yearbook of the Law Department, 2021)
The present study brings to the reader’s attention an extremely important fact for the European patent system – the beginning of the work of the Unified Patent Court. On January 19, 2022, the Protocol for the Preliminary Implementation of the Agreement on the Unified Patent Court entered into force, and it is expected to start functioning by the end of 2022 and the beginning of the following year. The article examines in historical order the creation and development of the European patent system, as well as the adopted legal acts outlining the new patent system of the European Union. The structure, competence and way of functioning of the Unified Patent Court have been clarified. Emphasis is placed on the advantages resulting from the introduction of the unified patent system, and above all on the role of the Unified Patent Court in unifying judicial practice in various patent disputes. The aim is to establish greater legal certainty in protecting the rights of patent holders. The opportunities and some of the problems that arise for Bulgarian enterprises since the introduction of the new patent system are indicated.